Integrasi Esensi Syura dalam Konsep Demokrasi Pancasila: Analisis Konstitusional Pasal 1 Ayat (2) dan Pasal 2 UUD 1945 - Wahyudi, Muhammad Haris Gifari (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
This study aims to analyze the integration of the essence of syura values in the concept of Pancasila Democracy through a constitutional analysis approach to Article 1 Paragraph (2) and Article 2 of the 1945 Constitution. The method used is normative legal research with a qualitative and comparative approach, examining primary legal materials such as the text of the constitution and QS. Ali ‘Imran 3:159, as well as secondary materials such as journals and tafsir books. The results of the study show that there is a significant philosophical meeting point between syura and Pancasila Democracy, particularly in the rejection of authoritarianism, the emphasis on deliberation to reach consensus as the heart of decision-making, and the recognition of a transcendent value framework that limits human sovereignty. Constitutional analysis reveals that the phrase “implemented in accordance with the Constitution” and the naming of the People's Consultative Assembly can be interpreted as the institutionalization of shura values such as justice, public interest, and moral accountability. Thus, the integration of shura values enriches the meaning of people's sovereignty and restores substantive democracy without changing the foundations of the state. This study recommends strengthening the ethics of deliberation in constitutional practice to realize more dignified and just public deliberation.